Sanctioning of Illegal and Dangerous Ruck Cleanouts During the 2018 Super Rugby Competition - Kraak, Wilbur; Bam, Jenna; Kruger, Stephanie; Henderson, Stephanie; Josias, Ugan; Stokes, Keith (Frontiers in Psychology, 2019)
Rugby is a high contact sport that results in many injuries. The majority of injuries at the senior and elite levels of rugby result from contact phases of play with around 10% of all match injuries associated with the ruck in professional and community rugby. Surveillance of legal and illegal ruck cleanouts and the sanctions imposed by referees will help identify whether referees are actually enforcing the law according to the law book, which will consequently contribute to the creation and implementation of further injury prevention strategies. Players should play the game in accordance with the laws of the game and be mindful of their own safety and that of others. It is the responsibility of those who coach or teach the game to ensure that players are prepared in a manner that ensures compliance with the laws of the game and in accordance with safe practices. Laws and law amendments are fundamental to the development of sport and are introduced for a variety of reasons. The aim of this study was to investigate the rate of sanctioning of illegal and dangerous ruck cleanouts during the 2018 Super Rugby competition by using Nacsport Basic+ video software. 120 round robin matches from the Super Rugby 2018 competition were coded and analysed. The analysis for the intra reliability showed an almost perfect (>0.95) agreement between all the performance indicators. In total, 22281 ruck cleanouts were coded, of which 9% (n=2111) were illegal ruck cleanouts, 93% were not sanctioned by the referees. 57% (1087 out of 1953) of the illegal ruck cleanouts not sanctioned by the referees were deemed dangerous. The majority of dangerous illegal ruck cleanouts not sanctioned by the referees were ‘shoulder charge’ (88%, n=280), ‘neck roll’ (86%, n=100) and ‘contact above the shoulder’ (81%, n=201). To aid injury prevention efforts in rugby, future studies should explore why referees are not sanctioning all illegal and dangerous ruck cleanouts as per the World Rugby Laws of the Game.